Endophytic extract Zhinengcong alleviates heat stress-induced reproductive defect in Solanum lycopersicum - Cui, Xiaoshuang; Liu, Shangjia; Zhang, Lina; Guo, Xinping; Li, Ting; Zhang, Xiaoyu; Wang, Qingbin; Zeng, Weiqing; Huang, Jiabao; Duan, Qiaohong; Cao, Yunyun (Frontiers in Plant Science, 2022)
High temperature negatively affects reproductive process significantly, leading to tremendous losses in crop quality and yield. Zhinengcong (ZNC), a crude extract from the endophytic fungus Paecilomyces variotii, has been shown to improve plant growth and resistance to biotic and abiotic stresses. We show here that ZNC can also alleviate heat stress-induced reproductive defects in Solanum lycopersicum, such as short-term heat-induced inhibition on pollen viability, germination and tube growth, and long-term heat stress-induced pollen developmental defects. We further demonstrated that ZNC alleviates heat stress by downregulating the expressions of ROS production-related genes, RBOHs, and upregulating antioxidant related genes and the activities of the corresponding enzymes, thus preventing the over accumulation of heat-induced reactive oxygen species (ROS) in anther, pollen grain and pollen tube. Furthermore, spraying application of ZNC onto tomato plants under long-term heat stress promotes fruit and seed bearing in the field. In summary, plant endophytic fungus extract ZNC promotes the reproductive process and yield of tomato plants under heat stress and presents excellent potential in agricultural applications.